Analisis Pemahaman Mahasiswa Prodi Pendidikan Matematika Terkait Kemampuan Matematika Siswa Menengah Pertama dan Menengah Atas Serta Faktor-Faktor yang Mempengaruhinya - Hizmi Wardani; Desniarti Desniarti; Ramadhani Ramadhani; Nana Yuniar (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to analyze the understanding of Mathematics Education Study Program students towards the mathematical abilities of Junior High School (SMP) and Senior High School (SMA) students, as well as the factors that influence them. This study uses a descriptive quantitative approach with 35 fifth semester students of the Mathematics Education Study Program as research subjects. Data were collected using a questionnaire compiled based on indicators of students' understanding of mathematical abilities, problem-solving and mathematical reasoning abilities, pedagogical reflections of prospective teachers, and internal and external factors that influence students' mathematical abilities. Data were analyzed descriptively using percentages and classified into understanding criteria. The results showed that students' understanding of junior high school students' mathematical abilities was in the good category with a percentage of 82.04%, understanding of high school students' mathematical abilities was 82.71%, understanding of problem-solving and mathematical reasoning abilities was 81.58%, students' pedagogical reflection was 81.18%, and understanding of factors that influence students' mathematical abilities was 81.49%. Overall, the research results indicate that students have a good understanding of their role as prospective mathematics teachers, although some areas still require strengthening, particularly understanding student difficulties with specific material and developing ongoing pedagogical reflection. These findings are expected to inform the evaluation and development of the curriculum for prospective mathematics teachers.